Strategi Dakwah dalam Masalah Sosial - Usman, Usman (Universitas Islam Negeri Imam Bonjol Padang, 2010)
“Dakwah Islam” is essentially a pious that actualization in a system of human activity in the lives of believers who conducted regularly to influence how to feel, think, act, and act. “Dakwah Islam”means all efforts to realize the true teachings of Islam in daily life. AIDS is one disease that affects many, and is transmitted by the perpetrators of atrocities in the midst of society. When the HIV virus has infected a person, means he is ready also to spread the seeds of this disaster to others.